Risk assessment of workers exposed to crystalline silica aerosols - Rokni, Mohammad; Mohammadyan, Mahmoud; Hashemi, Seyyed Taghi; Asadi, Seyyed Mohammad; Boogaard, Peter J.; Heibati, Behzad; Yetilmezsoy, Kaan; Abdul-Wahab, Sabah Ahmed (TAYLOR & FRANCIS INC, 2016)
This study was conducted to determine the concentration of airborne respirable crystalline silica (ARCS) particles and to evaluate its risk level among workers employed in eight different workplaces in Iran. They included sandblasting operations, ceramic production, sand and gravel work, brick production, asphalt manufacturing, foundry operation, glass making, and stone cutting. Personal exposure to ARCS was measured in randomly selected samples from each workplace. The maximum and minimum average of ARCS concentration in the eight workplaces were observed in foundry operation (0.338 +/- 0.110mg/m(3)) and glass manufacturing (0.125 +/- 0.093mg/m(3)), respectively. The average concentration of ARCS in all assessed working conditions were higher than the permitted limit of occupational contact recommended by Technical Committee of the Iranian Ministry of Health, treatment and medical education (0.025mg/m(3)). Overall, the results showed a serious lack of control in Iranian industries with respect to workers' exposures to ARCS.
Keywords: crystalline silica; exposure rate; respirable particles; risk assessment; workers' exposure; DUST; Biodiversity & Conservation; Environmental Sciences & Ecology